Behavior of Strengthened Composite Prestressed Concrete Girders under Static and Repeated Loading. (27th December 2017) - Allawi, Abbas AbdulMajeed
Abstract : The use of external posttensioning technique for strengthening reinforced concrete girders has been considerably studied by many researchers worldwide. However, no available data are seen regarding strengthening full-scale composite prestressed concrete girders with external posttensioned technique under static and repeated loading. In this research, four full-scale composite prestressed I-shape girders of 16 m span were fabricated and tested under static and repeated loading up to failure. Accordingly, two girders were externally strengthened with posttensioned strands, while the other two girders were left without strengthening. The experimental tests include deflection, cracking load, ultimate strength and strains at midspan, and loading stages. Test results were compared with the design expressions mentioned in AASHTO LRFD specifications and ACI 318-2014 code. Also, a nonlinear analysis was conducted using the finite element method (FEM). The presented analysis models were verified by comparing the model results with test results. The general theme abstracted from both experimental tests and numerical analysis reflects that the performance and procedure of strengthening with external prestressing of girders were found to be effective in increasing the load carrying capacity of the strengthened girders.